THE EVALUATION OF CONVENTIONAL AND DIGITAL RADIOGRAPH FOR RADIOPACITY ASSESSMENT OF RESTORATIVE MATERIALS: -EVALUASI RADIOGRAF KONVENSIONAL DAN DIGITAL DALAM MENILAI RADIOPASITAS BAHAN RESTORASI - Manja, Cek Dara; Harahap, Kholidina Imanda (TALENTA, 2018)
Radiopacity is an important characteristic for restorative materials as dentists have got different abilities in interpreting a lesion or caries in a radiograph. The enforcement of secondary caries diagnosis is a challenge for dentists because they often mistake the diagnosis for restorative materials with low radiopacity. This study aims to determine the differences in the average radiopacity values of certain restorative materials by using conventional and digital radiographs. Moreover, to know the right types of radiographs in distinguishing between radiopacity of certain restorative materials and radiodensity of secondary caries. This is an analytical descriptive study with cross sectional design. The sample was divided into 10 groups of 6, which is dental radiograph filled with glass ionomer cement, resin modified glass ionomer cement, nanofiller and micro hybrid composites as well as teeth with secondary caries which were obtained from conventional and digital radiographs. Next, conventional and digital radiographs were interpreted by observations of 5 dental specialists in which measurement was done by using Image J software to get the average radiopacity values of secondary caries and each restorative material. The results showed that the average radiopacity values for glass ionomer cement are 177.633 ± 6.465 and 187.879 ± 9.305, resin modified glass ionomer cement are179.498 ± 5.597 and 192.078 ± 11.006, composite nanofillers are 194.847 ± 4.952 and 184.401 ± 9.170, microhybridcomposites are 189.109 ± 4.251 and 179.585 ± 6.809, finally secondary caries are 161.772 ± 9.256 and 109.988 ± 7.684 for conventional and digital radiographs respectively. Then the data was analyzed by using T test with significance value of p <0.05. As a conclusion, this study shows no significant difference in the radiopacity of four restorative materials if compared between conventional and digital radiographs while digital radiograph shows significant difference between radiopacity values of restorative materials and secondary caries. Whereas, conventional radiograph does not show significant difference between restorative materials and secondary caries. Radiopacity is an important characteristic for restorative materials as dentists have got different abilities in interpreting a lesion or caries in a radiograph. The enforcement of secondary caries diagnosis is a challenge for dentists because they often mistake the diagnosis for restorative materials with low radiopacity. This study aims to determine the differences in the average radiopacity values of certain restorative materials by using conventional and digital radiographs. Moreover, to know the right types of radiographs in distinguishing between radiopacity of certain restorative materials and radiodensity of secondary caries. This is an analytical descriptive study with cross sectional design. The sample was divided into 10 groups of 6, which is dental radiograph filled with glass ionomer cement, resin modified glass ionomer cement, nanofiller and micro hybrid composites as well as teeth with secondary caries which were obtained from conventional and digital radiographs. Next, conventional and digital radiographs were interpreted by observations of 5 dental specialists in which measurement was done by using Image J software to get the average radiopacity values of secondary caries and each restorative material. The results showed that the average radiopacity values for glass ionomer cement are 177.633 ± 6.465 and 187.879 ± 9.305, resin modified glass ionomer cement are179.498 ± 5.597 and 192.078 ± 11.006, composite nanofillers are 194.847 ± 4.952 and 184.401 ± 9.170, microhybridcomposites are 189.109 ± 4.251 and 179.585 ± 6.809, finally secondary caries are 161.772 ± 9.256 and 109.988 ± 7.684 for conventional and digital radiographs respectively. Then the data was analyzed by using T test with significance value of p <0.05. As a conclusion, this study shows no significant difference in the radiopacity of four restorative materials if compared between conventional and digital radiographs while digital radiograph shows significant difference between radiopacity values of restorative materials and secondary caries. Whereas, conventional radiograph does not show significant difference between restorative materials and secondary caries.